2013
DOI: 10.1111/cbdd.12064
|View full text |Cite
|
Sign up to set email alerts
|

Natural Products as Sources of New Fungicides (I): Synthesis and Antifungal Activity of Acetophenone Derivatives Against Phytopathogenic Fungi

Abstract: Several series of 45 acetophenone derivatives bearing various alkyl or benzyl substituents were conveniently synthesized and their structures characterized by (1)H and (13)C NMR spectroscopy, HRMS and single-crystal X-ray analysis. Their in vitro antifungal activities against a panel of phytopathogenic fungi were evaluated by mycelial growth rate assay. Of them, 12 derivatives (e.g., 3a-c, 4c and 4e) exhibited more potent antifungal effects on some phytopathogens than a commercial fungicide hymexazol as positi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
21
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(24 citation statements)
references
References 19 publications
1
21
0
2
Order By: Relevance
“…Recent reports have shown that the co-occurrence of a hydroxyl and a lipophilic alkyl group in ortho relationship is helpful for the antifungal activity (Ma et al 2013). Our results match these findings, because 4HMBA possess the ortho relationship between hydroxyl and prenyl groups.…”
Section: Discussionsupporting
confidence: 91%
“…Recent reports have shown that the co-occurrence of a hydroxyl and a lipophilic alkyl group in ortho relationship is helpful for the antifungal activity (Ma et al 2013). Our results match these findings, because 4HMBA possess the ortho relationship between hydroxyl and prenyl groups.…”
Section: Discussionsupporting
confidence: 91%
“…18 Acetophenones are reported to exhibit various biological properties such us herbicidal, antimicrobial and antioxidant activities. 19 To the best of our knowledge, only methyl phenyl ketone has been assayed against nematodes, and the compound proved to be inactive. 20 Chalcones, (E)-1,3-diaryl-2-propen-1-ones, are also products of the flavonoid pathway and are characterised by two aromatic rings bearing a diverse array of substituents.…”
Section: Introductionmentioning
confidence: 99%
“…Apesar de ainda não haver dados sobre a atividade antifúngica do EPHO, outras moléculas da classe das acetofenonas e derivados já demonstraram atividade contra diferentes fungos, incluindo C. albicans, sugerindo também que sua ação farmacológica provavelmente ocorra devido a inibição da formação da parede celular fúngica além de impedir o desenvolvimento de estruturas de virulência como pseudohifas [19,32].…”
Section: Resultsunclassified
“…Outros compostos da classe das acetofenonas já demonstraram excelente efeito antifúngico contra fungos dermatófitos, com concentrações inibitórias até 16 vezes menores do que as de antifúngicos-padrão como a anfotericina B, apontando estratégias de modificação molecular como quaternização para aprimorar o efeito biológico [18]. Ma et al (2013) [19], apresentaram um possível grupo farmacofórico, indicando que a ocorrência simultânea de um substituinte metahidroxila fenólica e um substituinte para-alquila lipofílico beneficiavam a atividade antifúngica das moléculas derivadas das acetofenonas.…”
Section: Figura 1: Estrutura Química Da 34-(metilenodioxi)-acetofenounclassified